Mycoplasma genitalium Biofilms Contain Poly-GlcNAc and Contribute to Antibiotic Resistance - Daubenspeck, James M.; Totten, Arthur H.; Needham, Jason; Feng, Monica; Balish, Mitchell F.; Atkinson, T. Prescott; Dybvig, Kevin (Frontiers in Microbiology, 2020)
Mycoplasma genitalium is an important etiologic agent of non-gonococcal urethritis (NGU), known for chronicity and multidrug resistance, in which biofilms may play an integral role. In some bacterial species capable of forming biofilms, extracellular polymeric substances (EPS) composed of poly-N-acetylglucosamine (PNAG) are a crucial component of the matrix. Monosaccharide analysis of M. genitalium strains revealed high abundance of GlcNAc, suggesting a biofilm-specific EPS. Chromatograms also showed high concentrations of galactose and glucose as observed in other mycoplasma species. Fluorescence microscopy of M. genitalium biofilms utilizing fluor-coupled lectins revealed differential staining of biofilm structures. Scanning electron microscopy (SEM) showed increasing maturation over time of bacterial “towers” seen in biofilm development. As seen with Mycoplasma pneumoniae, organisms within fully mature M. genitalium biofilms exhibited loss of cell polarization. Bacteria associated with disrupted biofilms exhibited decreased dose-dependent viability after treatment with antibiotics compared to bacteria with intact biofilms. In addition, growth index analysis demonstrated decreases in metabolism in cultures with disrupted biofilms with antibiotic treatment. Taken together, these data suggest that M. genitalium biofilms are a contributing factor in antibiotic resistance.